PENGARUH KETINGGIAN TEMPAT DAN MUSIM TERHADAP FLUKTUASI APHID PADA TANAMAN KENTANG - Hafiz Fauzana; Syafri Syafei; Ahsol Uasyim; Musliar Kasim (Jurnal Sagu, 2002)
The study on the innuence of altitude and season toward aphid population fluctuation inpotato plant. This research was carried out in Rimbo Data, Aia Butunibuak and Sukaraniiareas. Aphid identification was done in Laboratory of Agronomy Study Program, Faculty ofAgriculture, Andalas University, Padang, and in the Research Hall of Fruit Plant, Solok. Theaphid population fluctuation was observed by capturing the aphid flying by installing threetraps of Moerickc tray put in the potato plantation in each area. Treatment of this researchwas in the difference of position altitude of the capture area, viz, Rimbo Data (1,700 mDPL), Aia Batunibuak (1.350 m DPL), and Sukaranii (1.000 in DPL). The research resultshowed that the aphid population in the potato plantation was lower in the area of RimboData (1.700 m DPL) compared with the area of Aia Baturnbuak (1,350 m DPL) and Sukarami(1.000 m DPL). The period witliout aphid was only found in the area of Rimbo Data atOctober, and January, The type of dominant aphid in Rimbo Data was Macrosiphumeiiphorbiae, in Aia Baturnbuak and Sukaranii were Aphis fabae.